Clinical characteristics and survival of 413 patients with systemic lupus erythematosus in southeastern areas of South Korea: A multicenter retrospective cohort study. (4th December 2019) - Koh, Jung Hee; Park, Eun‐Kyoung; Lee, Han‐Na; Kim, Yunkyung; Kim, Geun‐Tae; Suh, Young Sun; Kim, Hyun‐Ok; Lee, Seung‐Geun
Abstract: Aims: To investigate demographic, clinical, laboratory, and immunological characteristics of patients with systemic lupus erythematosus (SLE) in southeastern areas of South Korea, and to perform survival analysis. Methods: We retrospectively evaluated 413 patients with SLE diagnosed in 3 tertiary rheumatology centers in South Korea from 1992 to 2016 by reviewing their medical charts. All patients fulfilled the 1997 revised American College of Rheumatology classification criteria for SLE. Results: Most patients were women (92%), and the mean (±standard deviation) age at diagnosis was 30.9 (±12.9) years. The most common clinical manifestation was leukopenia (74.3%), followed by lymphopenia (73.6%), arthritis (59.1%), malar rash (48.4%), thrombocytopenia (46.5%), oral ulcer (35.1%), and biopsy‐proven lupus nephritis (31.2%). Anti‐nuclear, anti‐double‐stranded DNA, anti‐Smith, and anti‐Ro antibodies were positive in 97.8%, 70.1%, 38.4%, and 63% of patients, respectively. Twenty (4.8%) patients died during a median follow‐up of 83 months, and the cumulative 5‐year and 10‐year survival rates were 96.9% and 95.5%, respectively. The major causes of death were infection (50%) and lupus flare‐up (50%). Male (hazards ratio [HR] = 7.19, P  = .001), pleuritis and/or pericarditis (HR = 3.28, P  = .012), childhood‐onset (HR = 3.57, P  = .012), and late‐onset (HR = 4.65, P  = .011) were independent risk factors for death. Compared with SLE cohorts in other ethnicities or countries, our patients tended to have a higher frequency of anti‐Ro antibodies and hematologic disorders. Conclusion: This study describes clinical features of SLE in South Korea and suggests a remarkable phenotypic heterogeneity of SLE.